PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INTRUCTION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 031 BANJAR XII KECAMATAN TANAH PUTIH - Susanti, Mira; Noviana, Eddy; Putra, Zetra Hainul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievment of social studies SD Negeri 031 Banjar XII fourth graderes still low with an average value of 61,76 and minimum completenness criteria (KKM) social studies is 70,00. Between students, amounting to 17 people only 8 students who achieve classical KKM with 47,06%. This research is Classroom Action Research (CAR), wich aims to improve the student achievement of social studies class fourth at SD Negeri 031 Banjar XII with implementation Model Problem Based Instruction (PBI). Formulation of the problem: is the implementation of model Problem Based Instruction (PBI) can improve students achievment of social studies at SD Negeri 031 Banjar XII fourth graderes?. The research was conducted on march 17, 2015 to april 3, 2015 by 2 cycles. Subjects were students of SD Negeri 031 Banjar XII fourth graderes, totalling 17 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. Activities of the teacher in the learning process in cycle I the first meeting to 58,33% and the second meeting improve to 79,17%. Cycle II first meeting and the second meeting improve 91,67% and the second meeting improve to 95,83%. Result of data analysis of students activities in the first meeting cycle I with the first meeting of an avarage of 54,17% and a second meeting improve to 66,67%. Cycle II first meeting improve 83,33% and the second meeting improve to 95,83%. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 61,76. In the first cycle improve an average of 70,58 with increase big as 14,28% and an impove in the second with an average of 83,52 with increase big as 35,23%. Result in the class fourth at SD Negeri 031 Banjar XII that the implementation of model problem based instruction can improve students achievement of social studies at fourth graderes SD Negeri 031 Banjar XII.Keywords: model PBI, students achievement the result of social studies